2019
DOI: 10.1161/jaha.118.011366
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Mitral Valve Pressure Gradient Is Predictive of Long‐Term Outcome After Percutaneous Edge‐to‐Edge Mitral Valve Repair in Patients With Degenerative Mitral Regurgitation (MR), But Not in Functional MR

Abstract: Background This study analyzed the effects on long‐term outcome of residual mitral regurgitation ( MR ) and mean mitral valve pressure gradient ( MVPG ) after percutaneous edge‐to‐edge mitral valve repair using the MitraClip system. Methods and Results Two hundred fifty‐five patients who underwent percutaneous edge‐to‐edge mitral valve repair were analyzed. Kaplan–Meier and Cox regression analyses were performed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 32 publications
2
39
1
Order By: Relevance
“…A recent study by Patzelt et al, evaluated the impact of postprocedural MG on outcomes. They found that a MG cutoff of 4.4 mmHg was predictive of outcomes in patients with degenerative MR but not in functional MR 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Patzelt et al, evaluated the impact of postprocedural MG on outcomes. They found that a MG cutoff of 4.4 mmHg was predictive of outcomes in patients with degenerative MR but not in functional MR 9 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Patzelt et al, evaluated the impact of postprocedural MG on outcomes. They found that a MG cutoff of 4.4 mmHg was predictive of outcomes in patients with degenerative MR but not in functional MR 9. The correlation between MG and LAP in relation to symptomatic improvement post-MitraClip is less established.…”
mentioning
confidence: 99%
“…Elevated mitral valve pressure gradient might increase left atrial pressure, of which the latter is associated with less improvement in 6MWD after MitraClip implantation [33]. A recent trial on MitraClip therapy for secondary MR did not show a correlation between postprocedural mitral valve pressure gradient and 6MWD, but with worse NYHA class [34]. Therefore, elevated mitral valve pressure gradient in women might be an important factor in the observed gender-specific difference.…”
Section: Gender-related Differences In Functional Outcome Of Mitraclip Therapymentioning
confidence: 99%
“…In MR, assessment of the valve, left ventricle, left atrium, chordae tendineae and papillary muscles are all important to determine the etiology of the disease. It is also crucial to determine the type of MR (primary or secondary, ischemic or nonischemic) due to the differences in treatment options and post-procedural prognosis (31)(32)(33). Past reports have suggested that successful repair for secondary MR was less likely in the presence of mitral valve (MV) deformation, global LV remodeling and local LV remodeling (34).…”
Section: What To Look For?mentioning
confidence: 99%